SEC of Simple Polymers with Molar Mass Detection in the Presence of Instrumental Broadening. Computer Simulation Study on the Recuperation of Unbiased Molecular Weight Distributions - Vega, Jorge Ruben (2001)
This theoretical work presents a correction procedure for calculating an unbiased MWD when analyzing a linear homopolymer by size exclusion chromatography with molar mass detection. The fractionation and the measurements are ideal, but the chromatograms are distorted by a nonuniform and skewed instrumental broadening (IB), and are contaminated with a zero-mean random noise. The main assumption is that the molecular weight calibration is linear in the chromatogram range. The following phenomenological procedure was proposed: (i) independently correct the mass- and molar mass chromatograms for IB through a robust inverse filtering technique; (ii) estimate the unbiased calibration from the ratio of the corrected chromatograms; (iii) adjust a straight line to the mid-values of that cal-ibration; and (iv) estimate the unbiased MWD from the linear calibration and the corrected mass chromatogram. For the chromatogram inversions, a minimum sized broadening matrix was selected and a singular value decomposition technique was applied. The following effects were evaluated: of an increased measurement noise, of uncertainties in the range of the measured chromatograms, and of systematic errors in the IB function. The method fails for very narrow MWDs.